Multicriterion optimization of space trusses with stiffness variation - Paczkowski, Witold M.; Jendo, Stefan (Computer Assisted Methods in Engineering and Science, 2023)
The paper discusses the discrete optimization problem in structural space truss design. The optimal structure should satisfy limit state capacity and serviceability conditions. If the serviceability conditions are violated, the structure is not eliminated from considerations but it is modified by increasing structural stiffness. Many different ways to increase the stiffness of the structure are considered. The cross-sectional areas of truss bars Ak picked from a catalogue of circular hollow sections T and a number of elements in the catalogue t are taken as discrete design variables. The stress, local stability, displacement (design) constraints as well as technological and computational constraints are taken into account. The mass of truss bars including that of joints as well as exploitation and maintenance costs are chosen as optimization criteria. A labour consumption corresponding with a number of elements in the catalogue t is minimized, i.e., it is also regarded as an optimization criterion. Sets of non-dominated (efficient) and compromise (Pareto optimal) solutions, and the preferable solution for space truss are found . The results are presented in the form of diagrams and tables.